(a-b/2) ( a²+ b²/4 + a/2 × b )
Answers
Answered by
1
Answer:
First of all let understand this:
“(a+b)^2=(a-b) ^2+4ab”
Therefore, (a^2+b^2)^2=(a^2-b^2)^2+4a^2b^2
Now, according to the question
a^2-b^2=4. And. ab=2
Putting the value in the derived equation,
(a^2+b^2)^2=(4)^2+4(2)^2
=16+16=32
a^2+b^2= 4√2. :-)
Step-by-step explanation:
Similar questions
Psychology,
3 months ago
Political Science,
3 months ago
Math,
3 months ago
English,
8 months ago
Math,
8 months ago
English,
1 year ago
Science,
1 year ago